Unveiling the Determinants of Digital Library Success: A HOT-Fit Analysis of E-Perpus Kota Depok - Nurul Janah; Hanin Salwa Salsabila Hidayati Nurrohman; Amalia Rahmah (Sistemasi: Jurnal Sistem Informasi, 2026)
E-Perpus Kota Depok is a digital library service provided by the Depok City Library and Archives Service to reach a wider community which can be accessed via smartphone by downloading this application via Play Store. Digital libraries are public services that support the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 on Quality Education and SDG 9 on Industry, Innovation, and Infrastructure. However, information system success is influenced not only by technological aspects but also by human and organizational factors. This study analyzes the determinants of the success of the E-Perpus Kota Depok digital library system using the Human-Organization-Technology Fit (HOT-Fit) model. A quantitative approach was employed using a survey involving 200 users of the E-Perpus Kota Depok application. Data were collected through an online questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that nine out of twelve hypotheses were significant. System Quality positively influenced System Use and User Satisfaction, while Information Quality significantly influenced User Satisfaction. Service Quality did not significantly affect System Use or User Satisfaction. In addition, organizational and human factors contributed significantly to Net Benefit. The model demonstrated strong predictive power, with System Use obtaining the highest R-Square value of 71.6%. The study provides practical insights for improving digital public library services, although it is limited to a single regional context.